An introduction to friendliness (mettā) Emotional intelligence and freedom in the Pāli discourses of the Buddha - Sangiacomo, Andrea (University of Groningen Press, 2022)
Friendliness (mettā in Pāli) is an emotional and intentional attitude of goodwill and non-aversion towards all sentient beings, including oneself. It is rooted in both feeling and understanding. In the Pāli discourses of the Buddha, friendliness is repeatedly stressed and encouraged for its numerous benefits. It supports and develops a form of emotional intelligence and provides an ideal pathway to explore deeper aspects of one's experience and their philosophical implications. Friendliness is best understood not in isolation, but rather in the broader context of the Buddha's teachings. In that context, it plays an essential role as a catalyst for the unfolding of the whole Buddhist path. Friendliness, then, can be a particularly interesting thread to follow in order to unpack the meaning and practical implications of the core teachings conveyed in the discourses. This introduction combines meditation practice, philosophy, and the reading of ancient texts in order to show how friendliness can function both as an entry point to explore the landscape of the discourses, and how that same landscape unfolds from the perspective disclosed by friendliness.